(untitled) (Al-Academy, 2024)
This study aims to investigate the way through which artists expressed the body in their works and deciding the artistic style in which Contemporary artists tackled that. Moreover, the study aims to identify the most important artistic, symbolistic, and aesthetic. The research used an analytical elements descriptive approach in tracking the presence of the body in modern art. The study shows that the works which has the body in every shape or form, it proved that the body is always present whether through pictograms during the modernist era and what’s before it while being a main part in the contemporary and modern works throughout history. The study also sheds a light on the Arabic and Islamic experience in the subject and how it was filled with caution and reservation on how the body existed in art in order to make sure that it was in line with Islamic guidelines and tradition. The study resulted in several recommendations regarding the expression of the body in its several philosophical and aesthetic dimensions in contemporary works. Since it’s a rich subject with several aspects, the artist managed to discuss it in several ways. The research recommends that researchers and artists should search more in the subject, especially in the artistic practices in the Arab and Islamic worlds since not a lot of research has been done on the subject In the end, it is very important that the body is tackled in a cautious manner since it’s a subject that’s hard to maneuver with all the Islamic and Arabic traditions, especially since the Omani experience is still new and started only with contemporary art and it is still learning from Arab and western experiences in order to grow and keep up with them